Importance of Plants in Terms of Sustainability in Building Bumper Zone in Farm Areas - Gülden Sandal Erzurumlu; Mustafa Boğa (Turkish Journal of Agriculture: Food Science and Technology)
With the effects of various human activities and global warming, pressures on plant species are increasing day by day, living species and living environments are adversely affected. In order to reduce and control these negative effects, a variety of regulatory ecological services are needed to provide both a nutrient environment for animals and to save and maintain their habitat. For this purpose, creating buffer zones at the borders of fence plants and farm areas can be used as a regional supporting mechanism. One of the most important criteria is to use plant species (from Legüminaceae families) which have high nutritional value for animals in farm buffer areas. The selected plants have many functions such as erosion prevention on sloping areas, nutrient retention, aesthetic area creation, flood prevention, odor control. They are the ones that constantly occupy the city's agenda with various environmental problems such as ensuring control of unwanted odors in farm areas and improving visual quality. In this study, it is aimed to determine the plant species that can be suggested to be used in a buffer zone which can be created in order to create aesthetic value in farm areas, to control odor problem and to contribute to studies to create nutrients and to protect ecology.